The Impact of Hyponatremia on the Severity of Childhood Tuberculous Meningitis - Salih, Rashid; Toorn, Ronald van; Seddon, James A.; Solomons, Regan S. (Frontiers in Neurology, 2022)
Introduction: Hyponatremia and/or hypoglycorrhachia are commonly encountered biochemical derangements during the acute stage of childhood tuberculous meningitis (TBM). Few studies have explored the correlation between these derangements and the staging of TBM disease (severity), or explored their role as biomarkers for vascular ischemic events, hydrocephalus, or seizures. Methods: We aimed to identify the prevalence and the correlation between serum hyponatremia (mild, moderate and severe) and/or hypoglycorrhachia in relation to clinical TBM features such as stage of disease, seizures and stroke in children diagnosed with definite and probable TBM, between 1985 and 2015, at Tygerberg Hospital, Cape town, South Africa. Results: The prevalence of hyponatremia was 344 out of 481 (71.5%) patients; 169 (49.1%) had mild hyponatremia, 146 (42.4%) moderate hyponatremia and 29 (8.4%) severe hyponatremia. Increasing severity of hyponatremia was associated with stroke (clinical persistent hemi- or quadriparesis with or without radiological infarcts), signs of brainstem dysfunction, cranial nerve palsies and non-communicating hydrocephalus (all p<0.05). The prevalence of hypoglycorrhachia was 72.9% (306 out of 420). Children with hypoglycorrhachia were more likely to have had longer symptom duration prior to admission (p=0.02), non-communicating hydrocephalus (p=0.05), and higher cerebrospinal white cell counts and protein concentrations (both p <0.01). Conclusion: Hyponatremia and/or hypoglycorrhachia occur in more than two-thirds of children with TBM. Increasing severity of hyponatremia is predictive of TBM disease complications such as stroke and non-communicating hydrocephalus. Cerebrospinal fluid (CSF) glucose depletion correlates with non-communicating hydrocephalus and increased CSF inflammation.